Crustal-scale folding: Palaeozoic deformation of the mt painter inlier, South Australia - Weisheit, A.; Bons, P.; Danišík, Martin; Elburg, M. (Geological Society Publishing House, 2014)
The Mt Painter Inlier (Northern Flinders Ranges, South Australia) was exhumed in the Yankaninna Anticline, in the hanging wall of the major NE-SW-running Paralana Fault System. Regional north-south compression resulted in SE-directed oblique and lateral ramping on to the rigid Curnamona Province. Formation of the crustal-scale anticline caused exhumation of up to 15 km of basement rocks in the core of the anticline. Currently exposed rocks reached the surface in Permian times. Folding and thrusting commenced between c. 500 and c. 450 Ma and lasted until the Permian Period. Contrary to previous studies, only a minor part of the deformation can be attributed to the c. 500 Ma Delamerian Orogeny, with most of the tectonic activity being contemporaneous with the Alice Springs and Lachlan Orogenies. New Permo-Triassic zircon and apatite (U-Th)/He ages, as well as a titanite fission-track age point to a long-lived nearsurface hydrothermal event that overprinted the basement and cover rocks. Hydrothermal reheating and burial below the Mesozoic Eromanga Basin sediments, to a depth of no more than 2 km, resulted in partial or full rejuvenation of the apatite (U-Th)/He system.